2007
DOI: 10.1103/physrevlett.98.117007
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Fermi Pockets in a New Excitonic Charge-Density-Wave Melted Superconductor

Abstract: A superconducting state (T c 4:2 K) has very recently been observed upon successful doping of the charge-density-wave (CDW) ordered triangular lattice TiSe 2 , with copper. Using state-of-the-art photoemission spectroscopy we identify, for the first time, momentum-space locations of doped electrons that form the Fermi sea of the superconductor. With doping, we find that kinematic nesting volume increases, whereas coherence of the CDW collective order sharply drops. In superconducting doping, as chemical potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
66
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 32 publications
10
66
2
Order By: Relevance
“…In particular, we confirm Cu is a donor contributing delocalized electrons at the Fermi level and shifting the chemical potential up in energy in agreement with previous ARPES results [19,20]. We observe a striking instability towards the formation of charge stripes at low Cu concentration (x < 0.02) and the formation of short-range ordered domains which tend to be phase shifted at higher Cu contents (x > 0.05).…”
supporting
confidence: 91%
“…In particular, we confirm Cu is a donor contributing delocalized electrons at the Fermi level and shifting the chemical potential up in energy in agreement with previous ARPES results [19,20]. We observe a striking instability towards the formation of charge stripes at low Cu concentration (x < 0.02) and the formation of short-range ordered domains which tend to be phase shifted at higher Cu contents (x > 0.05).…”
supporting
confidence: 91%
“…[43] Intercalation with Cu atoms shifts the chemical potential of 1T-TiSe 2 by 0.1 eV. [53,54] Since the circumstances in the pristine material are nearly ideal for the formation of excitons, they deteriorate quickly upon intercalation, leaving a dominant role for the phonons in the CDW formation in this part of the phase diagram. As explained above, such a scenario naturally leads to a superconducting dome centered around the critical value of intercalation.…”
Section: Hybrid Phonon-exciton Modelmentioning
confidence: 99%
“…Photoemission studies have shown that the CDW order parameter microscopically competes with superconductivity in the same band. 3 In addition, previous work suggests that the CDW is suppressed by increasing the chemical potential, while superconductivity is enhanced by the increasing density of states (DOS).…”
Section: -5mentioning
confidence: 99%